Assessment of Resection Margins in Bone Tumor Surgery. (10th December 2020) - Malherbe, Corentin; Crutzen, Bernard; Schrooyen, Jean; Caruso, Giovanni; Lecouvet, Frédéric; Detrembleur, Christine; Schubert, Thomas; Docquier, Pierre-Louis
Abstract : Limb salvage surgery is now the preferred procedure for bone tumor surgery. To decrease the risk of local recurrence, it is crucial to obtain adequate resection margins. The obtained margins must be evaluated postoperatively because they influence what treatment is given subsequently when margins are not adequate (e.g., surgical revision and radiotherapy). The study aims to evaluate margin assessment of tumor specimen by MRI compared to conventional histology (to establish the viability of using MRI) and assess the accuracy of a patient-specific instrument when narrow margins were aimed. The resection margins in 12 consecutive patients that were operated on for bone tumor resection were prospectively analyzed using three methods: MRI of the resection specimen, macroscopic evaluation of specimen slices, and microscopic pathological evaluation. The assessments were qualitative (R0, R1, and R2) and quantitative (distance in mm). MRI, macroscopic, and microscopic margins generated similar results for both the qualitative (all resections were R0) and quantitative assessments. The median error in safe margins was 2 mm with a surgical guide (PSI) and 5 mm without a surgical guide. Local recurrences were not detected after a mean follow-up period of 3.7 years (range, 2.1–5 years); however, four patients died during the study. In conclusion, MRI is a valuable tool for assessing safe margins. When specimens are not available for pathological assessment (e.g., extracorporeally irradiated autograft or autoclaved autograft), MRI could be used to evaluate margins. In particular, when tumor volume is high, MRI could also help to focus the pathological examination on areas of concern.